Current and emerging drugs for acute bacterial skin and skin structure infections: an update. (September 2014) - Kollipara, Ramya; Downing, Christopher; Lee, Michael; Guidry, Jacqueline; Curtis, Stephen; Tyring, Stephen
<x xml:space="preserve">Abstract</x> Introduction: Antibiotic resistance, the emergence of multidrug-resistant bacteria and the exponential rise of methicillin-resistant Staphylococcus aureus (MRSA) acute bacterial skin and skin structure infections (ABSSSI) pose a great threat to the public health. In order to combat these threats, development of new antibiotics is vital and measures to decrease antibiotic resistance should be prioritized. Areas covered: This manuscript provides an overview of the current FDA-approved antibiotics and the antibiotics in development for MRSA ABSSSI. Expert opinion: A great need exists currently for novel antibiotics to combat multidrug-resistant MRSA. As clinicians, it is imperative to implement proper management in order to reduce antibiotic resistance.